The emergence of Contact Improvisation in the aesthetic-political laboratory of the 60s and 70s - Singer, Mariela (Revista Brasileira de Estudos da Presença, 2022)
This text reflects on the emergence of contact improvisation and the changes generated by postmodern dance in the American aesthetic-political context of the 60s and 70s. New modes of dance production developed by the New York neo-avant-garde of that period are addressed; the experimental attitude of the artists; and their interest in collaborative forms, among others. Based on the research results of my doctoral thesis, the literature on an emblematic discipline of postmodern dance, about which there are few publications in Spanish, is expanded. Further study may open imaginative horizons for new laboratory practices.